(untitled) (Research, Society and Development, 2020)
The machining process is the method more efficient and effective in creation fine parts in which there are many details in need quality and precision. However, there is a strong influence of the temperature in process, due the heat dissipation in the region of contact between the part and the tool. Currently, it is desired to achieve the highest productivity with the lowest expenditure, in the context of this work, the purpose is to increase the life of the cutting tool, and with the application of coating in the cutting region of the tool, it will be possible achieve these improvements that would provide less wear of the tool, achieving higher cutting speeds without increasing the temperature, preserving the integrity of the tool, which would eliminate financial expenses with constant changes of inserts and tools, reducing costs to the company and increasing its productivity. Thus, the research project studies about the termical influence in the coating on the cutting tool, using numerical simulation in a commercial software COMSOL Multiphysics® version 5.3a. It as also estimated the heat flux using the inverse technique of the melhod in the specified function, written using the MATLAB® package, which it was used for obtain the heat variable flux, used for obtain the numeric temperature for a cutting tool coasting in the Titanium Nitride (TiN) with thickness of 20 microns, and later compared wich the uncoated tool.